L‐Cysteine metabolism and its nutritional implications. Issue 1 (12th June 2015) - Yin, Jie; Ren, Wenkai; Yang, Guan; Duan, Jielin; Huang, Xingguo; Fang, Rejun; Li, Chongyong; Li, Tiejun; Yin, Yulong; Hou, Yongqing; Kim, Sung Woo; Wu, Guoyao
Abstract : l ‐Cysteine is a nutritionally semiessential amino acid and is present mainly in the form ofl ‐cystine in the extracellular space. With the help of a transport system, extracellularl ‐cystine crosses the plasma membrane and is reduced tol ‐cysteine within cells by thioredoxin and reduced glutathione (GSH). Intracellularl ‐cysteine plays an important role in cellular homeostasis as a precursor for protein synthesis, and for production of GSH, hydrogen sulfide (H2 S), and taurine.l ‐Cysteine‐dependent synthesis of GSH has been investigated in many pathological conditions, while the pathway forl ‐cysteine metabolism to form H2 S has received little attention with regard to prevention and treatment of disease in humans. The main objective of this review is to highlight the metabolic pathways ofl ‐cysteine catabolism to GSH, H2 S, and taurine, with special emphasis on therapeutic and nutritional use ofl ‐cysteine to improve the health and well‐being of animals and humans.